Hubungan Minat Konsumen Dengan Keputusan Pembelian Rumah Subsidi Pada Perumahan Grand Raya Korpri Residence Bengkulu - Mulyadi Mulyadi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study was to determine the relationship between consumer interest and the decision to purchase subsidized housing at the Grand Raya Korpri Residence Housing. The analytical method uses Spearman's rank correlation and hypothesis testing. The number of samples studied was 59 customers. Based on the results of the study, it was obtained that respondents' perceptions of the consumer interest variable obtained an average value of the consumer interest variable in subsidized housing Grand Raya Korpri Residence was 3.87, the value was between the interval 3.41 - 4.20, good criteria while respondents' perceptions of the the decision to purchase subsidized housing Grand Raya Korpri Residence Housing can be seen that the average number of respondents' answers is 3.94, the value is between the interval 3.41 – 4.20, good criteria, meaning that consumers feel that consumers have made the right decision to make purchase of subsidized housing at the Grand Raya Korpri Residence Housing. The value of the correlation coefficient obtained by the value of rho count ( ) = 0.749 means that the relationship between consumer interest and the decision to purchase subsidized housing at the Grand Raya Korpri Residence Housing is strong, because the correlation value is in the coefficient interval 0.600 – 0.799. Based on the hypothesis test obtained t count > t table (8.534 > 1.662). meaning that there is a significant relationship between consumer interest and the decision to purchase subsidized housing at the Grand Raya Korpri Residence Housing.